Conversion of borate glass microspheres to hollow biphasic calcium phosphate ceramic microspheres for bone defects. Issue 12 (3rd August 2022) - Shen, Youqu; Semon, Julie A.; Brow, Richard K.
Abstract: Hollow biphasic calcium phosphate (BCP) microspheres with different fractions of nanocrystalline hydroxyapatite (HA) and β‐tricalcium phosphate (β‐TCP) were prepared, and their in vitro and in vivo reactivity were assessed. The microspheres were prepared by reacting soluble borate glass microspheres in phosphate solutions (0.1‐ or 0.25‐M K2 HPO4 ) with different values of pH (7–12) to produce hollow calcium‐deficient hydroxyapatite (CDHA) microspheres with Ca/P ratios that increased with solution pH. Heating the hollow CDHA microspheres to 800°C produced hollow, nanoporous BCP microspheres with ratios of nanocrystalline HA and β‐TCP that correspond to the Ca/P ratio of the CDHA precursors. Hollow BCP microspheres with a greater fraction of β‐TCP released calcium ions most quickly in a K‐acetate acidic buffer solution, consistent with their greater bioactivity in the in vivo tests. CDHA and BCP microspheres converted to nanocrystalline carbonated HA when immersed in 37°C simulated body fluid. Hollow CDHA and BCP microspheres were implanted in rat calvarial defects, and after 8 weeks, the BCP microspheres with a β‐TCP/HA ratio of 70/30 (by weight) promoted a greater fraction of new bone formation (33% ± 7%) compared to BCP microspheres with a β‐TCP/HA ratio of 44/56 (20% ± 9%) and compared to the respective CDHA precursor microspheres (17% ± 4%, 17% ± 5%). Bone formation was not observed in the subcutaneous implants of any types of these hollow microspheres, after 8 and 12 weeks, and the more reactive BCP microspheres (β‐TCP/HA = 70/30) were associated with significantly more blood vessel formation in the subcutaneous implants. These results indicate that the properties of hollow BCP microspheres can be tailored by their processing conditions and are useful as scaffold materials for tissue regeneration.